Nilai, Size, Profitabilitas Perusahaan dan Praktik Perataan Laba - Winanda, I Ketut; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2021)
The capital market in Indonesia is currently growing, so that competition between companies is increasing. The company will try to increase the value of the company in order to attract investors to invest in the company. Management realizes that attention investors tend to only focus on profit, so managers are encouraged to practice income smoothing. This study aims to obtain empirical evidence of the influence of firm value, firm size and profitability on income smoothing practices in banking companies listed on the Indonesia Stock Exchange for the 2016-2018 periode. The number of samples selected in banking companies is as many as 31 companies, using the purposive sampling method. The data analysis technique used is a logistic regression analysis and the results showed that the firm value and firm size had a positive effect on income smoothing practices, while the profitability did not effect the income smoothing practice. Keywords: Income Smoothing; Firm Value; Firm Size; Profitability.